Satisfaction as Mediators of the Relationship between Motivation and Loyalty of Diving Tourists to Bali - Suardana, I Wayan; Gde Bendesa, I Komang; Antara, Made (E-Journal of Tourism; Volume 1 Number 1 (March 2014), 2014)
This study was conducted to determine the relationship between extrinsic motivation, satisfaction with the product loyalty and loyalty to the service provider either directly or indirectly. Intrinsic and extrinsic motivations of tourists were used as predictors in determining the tourist loyalty through satisfaction. The model adopted was tested on 250 travelers who had ever been diving in Bali with structural equation modeling (SEM). The empirical results showed that the causal relationship between intrinsic motivation, extrinsic motivation, and satisfaction with service loyalty and product loyalty could be confirmed. Satisfaction became a full media on the relationship between motivation and loyalty. In this model, it could be proved that there was a positive effect of service loyalty on product loyalty. This study contributes to the development of tourist loyalty which should pay attention to tourist satisfaction arising from intrinsic and extrinsic motivation of tourists. Tourist strong motivation to do diving would have an impact on the perceived satisfaction so that tourists have loyalty in service provider and loyal to the diving tourism product shown by intending to return to Bali and would recommend it to others.
Keywords: motivation, satisfaction, product loyalty and service loyalty